2020
DOI: 10.1111/hae.14082
|View full text |Cite
|
Sign up to set email alerts
|

The societal burden of haemophilia A. III – The potential impact of emicizumab on costs of haemophilia A in Australia

Abstract: IntroductionEmicizumab is a humanized monoclonal modified IgG4 antibody with bispecific antibody structure bridging Factor IXa and Factor X. Emicizumab has demonstrated efficacy and safety in adults, adolescents and paediatrics with HA, with or without inhibitors to Factor VIII (FVIII). There is currently no evidence that reports on the potential impact of the introduction of emicizumab on the societal costs of haemophilia A (HA). The purpose of this study was to explore the cost impact associated with the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In a non-ITI setting, pharmacoeconomic models have recently shown that prophylaxis with emicizumab for PsHAhri is associated with reduced costs of treatment of HA compared to prophylaxis with BpA. [21][22][23] An Australian study evaluated the impact of emicizumab on societal costs, based on changes in the direct and indirect costs incurred by people with moderate or severe HA. 22 The first year of emicizumab reduced annual costs associated with BpA by 92.0%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a non-ITI setting, pharmacoeconomic models have recently shown that prophylaxis with emicizumab for PsHAhri is associated with reduced costs of treatment of HA compared to prophylaxis with BpA. [21][22][23] An Australian study evaluated the impact of emicizumab on societal costs, based on changes in the direct and indirect costs incurred by people with moderate or severe HA. 22 The first year of emicizumab reduced annual costs associated with BpA by 92.0%.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] An Australian study evaluated the impact of emicizumab on societal costs, based on changes in the direct and indirect costs incurred by people with moderate or severe HA. 22 The first year of emicizumab reduced annual costs associated with BpA by 92.0%. 22 Compared to prophylaxis with BpA, the overall budget reduction of prophylaxis with emicizumab for people with HA and inhibitors who failed ITI was €45.4 million in a 3-year horizon (PPP US$56.8 million, calculated as mentioned before), according to an Italian study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations